Racial Differences in the Link between Alcohol Expectancies and Adolescent Drinking - Banks, Devin E. (Addict Behav, 2016)
INTRODUCTION: Alcohol expectancies are important determinants and predictors of adolescent alcohol use. Research with African Americans has shown that the endorsement of positive alcohol expectancies differs from that of Whites during childhood and predicts different alcohol outcomes during young adulthood. However, limited research has explored racial differences in the relationship between expectancy endorsement and alcohol use in school-aged adolescents. The current study examines the effect of White or African American race on the relationship between positive alcohol expectancies and alcohol use. METHODS: Participants were 104 adolescents ages 12–18 who identified as either non-Hispanic White or non-Hispanic African American. Participants completed self-report measures of alcohol consumption and positive social alcohol expectancies. RESULTS: Preliminary analyses revealed no racial differences in alcohol expectancies or consumption. However, race moderated the relationship between alcohol expectancies and alcohol use such that more positive expectancies predicted alcohol use among White youth, but not African American youth. CONCLUSIONS: These results suggest that alcohol expectancies, which were thought to be important mediators of the relationship between social and personality factors and adolescent alcohol use may not be as impactful for African Americans. Future research should focus on identifying factors posing unique risk for alcohol consumption in this population.